THE INTEGRATION OF ENGLISH INTO KITAB KUNING INSTRUCTION AT AQOBAH INTERNATIONAL SCHOOL JOMBANG - Wibisono, Muhamad Iqbal; Dewi, Dewimah Putri Tazkiyah; Machali, Imam (LPPM Universitas Bina Bangsa, 2026)
This study analyzes the processes, strategies, challenges, and sustainability of English integration in kitab kuning instruction at Aqobah International School, Jombang. Using a qualitative case study design, the research involved four informants (one director and three students) selected through purposive sampling. Data were collected via in-depth interviews and document analysis. Findings reveal systematic integration design through structured planning involving pesantren leadership, gradual implementation using a tiered system, and support from a bilingual ecosystem based on the Cambridge International curriculum. The main challenges were technical-linguistic in nature, including the complexity of translating Arabic terminology into English, difficulties in selecting appropriate language registers, and adaptation from the pegon script to the Latin alphabet. These challenges were successfully mitigated through strategies such as content limitation, peer learning, and weekly formative evaluation. The program enhances santri’ bilingual competence for international da’wah, although it requires further strengthening of educators’ capacity, particularly in mastering bilingual kitab kuning terminology.